Nonlinear Aeroelastic Modeling of a Folding Wing Structure. (May 2019) - Li, Peicheng; Ni, Yingge; Hou, Chi; Wan, Xiaopeng; Zhao, Meiying
Abstract: The nonlinear aeroelastic response of a folding wing with the hinge free-play nonlinearity is investigated. A nonlinear structural dynamic model is established based on the modal synthesis of free-substructures by modification of the connected relationships, and is unnecessary to re-establish it if the stiffness changes. The nonlinear aeroelastic equation is obtained by rational function approximation of the unsteady aerodynamic force, and solved by Runge-Kutta method to predict the aeroelastic response of the folding wing. The results show that the free-play at hinges changes the aeroelastic characteristic of the folding wing, leading to the occurrence of the limit cycle oscillation within a certain velocity range. Moreover, the sensitivity to the free-play is different for the inboard and outboard hinges. If the free-play is controlled within a certain value, the motion of nonlinear aeroelastic system of the folding wing can be considered linear approximately.